The iron-regulated staphylococcal lipoproteins - Sheldon, Jessica; Heinrichs, David (Frontiers in Cellular and Infection Microbiology, 2012)
Lipoproteins fulfill diverse roles in antibiotic resistance, adhesion, protein secretion, signaling and sensing, and many also serve as the substrate binding protein (SBP) partner to ABC transporters for the acquisition of a diverse array of nutrients including peptides, sugars, and scarcely abundant metals. In the staphylococci, the iron-regulated SBPs are significantly upregulated during iron starvation and function to sequester and deliver iron into the bacterial cell, enabling staphylococci to circumvent iron restriction imposed by the host environment. Accordingly, this subset of lipoproteins has been implicated in staphylococcal pathogenesis and virulence. Lipoproteins also activate the host innate immune response, triggered through Toll-like receptor-2 (TLR2) and, notably, the iron-regulated subset of lipoproteins are particularly immunogenic. In this review, we discuss the iron-regulated staphylococcal lipoproteins with regard to their biogenesis, substrate specificity, and impact on the host innate immune response.